أثر سياسة التحرير الاقتصادي في التعليم العام في السودان: دراسة حالة ولاية النيل الابيض خلال الفترة ( ۲۰۰۱ م - ۲۰۰۹م) - د. رشيدة عباس العوض محمد صالح (White Nile Journal for Studies and Research, 2024)
The aim of the research is to know the impact of the economic liberalization policy on education in White Nile State. The problem of the research was that education in White Nile State is plagued by a low level of education resulting from the lack of trained and qualified educational personnel, the lack of preparation of the educational environment and the weakness of educational services, among the most important results reached. It is researched that the economic liberalization policy has a positive impact on non-governmental education, and it also has a negative impact on the decline in the level of government education. The most important recommendations are paying attention to government schools and providing educational services to them, increasing the budget directed to government education, improving the educational environment, and providing textbooks for students. Keywords: economic liberalization, public education, private education, education services.